2004
DOI: 10.1002/pon.820
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and job satisfaction of cancer care workers

Abstract: The findings of this research suggest that the current workplace environment is having a negative impact on the well-being of systemic therapy staff, and may have consequences in terms of quality of patient care. Personnel identified system changes that they felt would help alleviate workload and resulting stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 29 publications
(30 reference statements)
4
89
0
6
Order By: Relevance
“…These data seemed to confirm the findings of another study (Ramirez et al, 1996) in which the causes of stress were classified as follows in order of importance: an excessive workload, bad organisation and poor resources, having managerial responsibilities and, finally, having to face the suffering of the patients. Many other authors have highlighted the role of perceived workload and organisational problems in the development of burnout (Cordes and Dougherty, 1993;Barni et al, 1996;Arnetz, 1997;Grunfeld et al, 2005). Over recent years, Maslach has forcefully argued that the main causes of the development of burnout are related more to the working environment than the individual, and that these aspects should be worked on in a preventive perspective (Maslach and Leiter, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These data seemed to confirm the findings of another study (Ramirez et al, 1996) in which the causes of stress were classified as follows in order of importance: an excessive workload, bad organisation and poor resources, having managerial responsibilities and, finally, having to face the suffering of the patients. Many other authors have highlighted the role of perceived workload and organisational problems in the development of burnout (Cordes and Dougherty, 1993;Barni et al, 1996;Arnetz, 1997;Grunfeld et al, 2005). Over recent years, Maslach has forcefully argued that the main causes of the development of burnout are related more to the working environment than the individual, and that these aspects should be worked on in a preventive perspective (Maslach and Leiter, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that longer working hours increases job strain among pediatricians in Japan according to the job demands-control model, and increases psychosomatic symptoms, possibly through an increase in job strain. The association between longer working hours and more psychosomatic symptoms may also be explained by greater work-home interference among subjects who worked longer hours, which is known to affect psychological distress 1,3,4,7,16,19,36) .…”
Section: Discussionmentioning
confidence: 99%
“…These include working hours 5,15,16) , overtime 17) , frequency of on-call duties 18) and work-home interference 1,3,4,7,19) . A few studies reported that long working hours were not associated with perceived stress at work 20) or psychological morbidity [21][22][23] .…”
mentioning
confidence: 99%
“…Oncologists described an increased level of stress with the longer consultations and delayed clinics, which suggests that the addition of gep testing and the increasing complexity of breast cancer management might contribute to broader negative issues in the day-to-day work of oncologists. Grunfeld et al 24 conducted a survey and 17 focus groups with Canadian cancer workers including medical oncologists, allied health professionals, and clerical staff. Survey results indicated that 46% of the oncologists endorsed having high job stress.…”
Section: Discussionmentioning
confidence: 99%